Utilization of Edible Wild Plants as Supplementary Source of Nutrition by Indigenous Communities in Kinnaur District, Himachal Pradesh, India - Singh, Joginder; Rajasekaran, A.; Negi, A. K.; Negi, S. P. (Indian Forester, 2019)
This study documents a total of 168 edible wild plant species belonging to sixty five families and 113 genera, utilized as a source of supplementary nutrition by the indigenous communities of the Kinnaur district, Himachal Pradesh. Of these, 150 species are angiosperms, four gymnosperms, two pteridophytes and twelve fungi. These plants were reported as edible by 279 informants of different age groups of both genders. Rosaceae was recorded as the most dominant family with twenty three edible wild plant species followed by Polygonaceae, Brassicaceae, Asteraceae and others. Herbs shared maximum growth form followed by shrubs, trees and climbers. Fruit parts were used maximum followed by tender leaves, seeds, underground parts, etc. Wild plant species reported as edible by maximum number of informants were listed as most used plants. Prunus cornuta was the most used plant followed by Hippophae salicifolia, Fragaria vesca, Elaeagnus parvifolia, etc. It has been observed that knowledge about the edibility of many wild plants is diminishing among young generations. Therefore, it is suggested that large scale awareness programmes on edible wild plants should be initiated. Paper highlights the need to prioritize important commercially potential species for conservation, domestication and development of valued added economic products.